Village Autonomy and Social Empowerment: The MSN-Approach Model in Tourism and Creative Economy Development Policies in Bromo Tengger Semeru National Park - Binada, Ulfa; Sinaga, Cristian Baik Budi Hasilohan; Chusnida, Nabilah Luthfiyah (Jurnal Magister Administrasi Publik, 2021)
The village government carries out village development in accordance with Law No. 6 of 2014 concerning Villages. One of the public policy models that can be implemented based on village autonomy is MSN-Approach with 3 dimensions namely mentality, systems, and networking. This study uses a qualitative approach with data collection techniques that include direct observation, in-depth interviews, document processing (written documents), and interactive dialogue through focus group discussions (FGD). This research was carried out in Wonokitri Village, Tosari District, Pasurun Regency. This research resulted in a community empowerment design carried out by the Bromo Tengger Semeru National Park Center (BB TNBTS) with the Tengger community in Wonokitri Village, especially the Hulun Hyang Farmer Group. The community empowerment focuses on the conservation of Edelweiss Flowers and the development of supporting destinations for the National Park Bromo Tengger Semeru. Through the Decree of the Head of the East Java SDA No. 110/K.2 /BIDTEK.1/11/2018, Hulun Hyang can officially cultivate Edelweiss Flowers ex-situ for customary, conservation, economic needs, and the opening of village tourist destinations. Furthermore, to accelerate village development and tourism in TN. Bromo Tengger Semeru, the village government collaborates with the private sector to manage the village's potential which includes jeep and homestay rentals through one-stop services (website and mobile application).